Didactization of Cultural Content in Foreign Language Instruction - Nikolčić, Nikolina; Pančevac, Milica; Mitrović, Milka (Norma, 2026)
The focus of this paper is the didacticization of cultural content (as defined by Jean-Claude Beaco) using authentic materials in foreign language instruction. Since learning a foreign language implies the acquisition of intercultural competencies, and as communicative competence is incomplete without appropriate intercultural competence, this paper promotes the significance of incorporating cultural phenomena in language teaching. Three instances of didactic approaches to cultural content in two foreign languages—Italian and English—are presented, suitable for implementation in classes at various levels of proficiency. Within the framework of discursive linguo-pragmatics (based on Claus Altmayer’s theory), and utilizing authentic materials, cultural phenomena from Italian and Serbian cultures were addressed through four stages: topic visualization, factual documentation, personalization, and linguistic analysis. In their foreign language classes, Serbian-speaking students expand their understanding of key concepts typical of the Italian-speaking world (such as mafia and coffee) and Serbian culture (including "Česhljanka," Serbian poetry, and The Battle of Kosovo). The application of authentic materials facilitates direct exposure to the authentic language and culture for students. This contemporary approach to foreign language teaching methodology fosters students’ research interests, team spirit, curiosity, and motivation for learning.